Progressive Vaccinia: Case Description and Laboratory-Guided Therapy With Vaccinia Immune Globulin, ST-246, and CMX001 - Lederman, Edith R. (Oxford University Press, 2012)
Progressive vaccinia (PV) is a rare but potentially lethal complication that develops in smallpox vaccine recipients with severely impaired cellular immunity. We describe a patient with PV who required treatment with vaccinia immune globulin and who received 2 investigational agents, ST-246 and CMX001. We describe the various molecular, pharmacokinetic, and immunologic studies that provided guidance to escalate and then successfully discontinue therapy. Despite development of resistance to ST-246 during treatment, the patient had resolution of PV. This case demonstrates the need for continued development of novel anti-orthopoxvirus pharmaceuticals and the importance of both intensive and timely clinical and laboratory support in management of PV.